Effect of Foliar Spraying with Humic and Fulvic Acid on Some indicators of vegetative growth and productivity of the two eggplant varieties - معروف, صبا (Submission and Review of Research -Biological Sciences Series, 2025)
The research was carried out during the agricultural season 2023 in a plastic house to investigate the effect of a commercial preparation of a mixture of humic and fulvic acids on two eggplant varieties "Karm" and "Thraya". The experiment included a control and three spraying dates after transplanting for each variety, and each treatment had three replicates according to the complete randomized block design. The results showed the following: Variety "Karm": Foliar spray treatments significantly outperformed the control in terms of leaf surface area and its index, number of fruits formed on the plant, productivity kg/m2; The third treatment (foliar spraying after 30 days of transplanting) gave the highest value for these indicators (17828 cm2, 2.223, 21.33 fruits/plant, 7.234kg/m2) while the lowest value was in the control (13650 cm2, 1.700, 13 fruits/plant, 4.182 kg/m2). This treatment also achieved the best results in terms of average fruit weight 271.3 g; it significantly outperformed the control which gave the lowest value 257.5g. as for the Thuraya variety The results showed the positive effect of foliar spraying with humic and fulvic acids and the third treatment achieved the highest value for average leaf surface area 18900 cm2 and its index 2.357, while the fourth treatment gave the best results in terms of: number of fruits 21 fruits/plant, average fruit weight 267.9 g, and productivity 7.035 kg/m2, superior to the control, which recorded the lowest values ​​for these indicators: 15820cm2, 1.973,12, 248 g, 3.718 kg/m2.